Fitness testing in soccer revisited: developing a contemporary testing battery - Taylor, J. M.; Madden, J. L.; Cunningham, L. P.; Wright, M. (Strength and Conditioning Journal, 2022)
Soccer match play dictates that players possess well-rounded physical capacities. Therefore, player physical development plans must consider developing several fitness components simultaneously. Effective individualization of training is likely facilitated with appropriate player profiling; therefore, developing a time-efficient and informative testing battery is highly relevant for practitioners. Advances in knowledge and technology over the past decade have resulted in refinements of the testing practices used by practitioners working in professional male and female soccer. Consequently, a contemporary approach to test selection and data analysis has progressively been adopted. Furthermore, the traditional approach of using a testing battery in a single day may now be outdated for full-time players, with a flexible approach to the scheduling of testing perhaps more suitable and time efficient. Here, guidance on testing for maximal aerobic, submaximal aerobic, linear and change of direction speed, and stretch-shortening cycle performance (i.e., jump testing) are presented for male and female players, with emphasis on time-efficient tests, while facilitating effective individualized training prescription. Normative and meaningful change data are presented to aid decision making and provide a reference point for practitioners. Finally, a time-efficient approach to scheduling fitness testing is presented, which complements daily training outcomes of a weekly periodization approach.